2021
DOI: 10.1155/2021/5536679
|View full text |Cite
|
Sign up to set email alerts
|

Sishen Pill Maintained Colonic Mucosal Barrier Integrity to Treat Ulcerative Colitis via Rho/ROCK Signaling Pathway

Abstract: Sishen Pill (SSP) is a classical prescription of traditional Chinese medicine and often used to treat gastrointestinal diseases, including ulcerative colitis (UC). However, its mechanism is still unclear. We aimed to determine the mechanism of SSP in the treatment of UC by investigating if it maintains the integrity of the intestinal mucosal barrier via the Rho A/Rho kinase (ROCK) signaling pathway. Administration of 2,4,6-trinitrobenzene sulfonic acid (TNBS) successfully induced chronic UC in rats, while the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 41 publications
(48 reference statements)
0
4
0
Order By: Relevance
“…The effects of a weakened epithelial barrier also extend to the mucosal barrier of the gut, seen in a study by Zhang et al which explored the Sishen Pill (SSP) which maintained the mucosal barrier of the colon by upregulating PTEN and subsequently downregulating the PI3K/Akt pathway [69]. Additionally, this study illustrates how PTEN downregulates of the Rho A/Rho kinase (ROCK) pathway which when stimulated decreases the integrity of the mucosal barrier.…”
Section: Pten As a Regulator Of Intestinal Barrier Dysfunctionmentioning
confidence: 71%
“…The effects of a weakened epithelial barrier also extend to the mucosal barrier of the gut, seen in a study by Zhang et al which explored the Sishen Pill (SSP) which maintained the mucosal barrier of the colon by upregulating PTEN and subsequently downregulating the PI3K/Akt pathway [69]. Additionally, this study illustrates how PTEN downregulates of the Rho A/Rho kinase (ROCK) pathway which when stimulated decreases the integrity of the mucosal barrier.…”
Section: Pten As a Regulator Of Intestinal Barrier Dysfunctionmentioning
confidence: 71%
“…Another study found that when the intestinal vascular barrier is damaged, intestinal bacteria are more likely to spread to the liver, promoting the formation of a pre-metastatic niche for “colon-liver” metastasis, thereby promoting the recruitment of metastatic cells ( Bertocchi et al, 2021 ). As mentioned earlier, Sishen Pills ( Zhang et al, 2021c ), schisandrin B ( Li et al, 2019b ), schisandrin C ( Kim et al, 2022 ), and corylin ( Wang et al, 2023f ) can regulate the secretion of intestinal epithelial tight junction proteins and mucin, repair damaged intestinal mucosal barriers and inhibit the progression of IBD ( Figure 3D ).…”
Section: Discussion On the Common Molecular Mechanism Of Sishen Pill ...mentioning
confidence: 82%
“…Briefly, it can 1) act on mammalian rapamycin target protein complex 1 (mTORC1) to promote protein synthesis and cell growth; 2) phosphorylate forkhead box O (FOXO) transcription factors, inhibit its transcriptional activity, and affect cell cycle, apoptosis, and metabolism; 3) inhibit the activity of glycogen synthase kinase 3 (GSK3) and regulate glycogen synthesis and cell cycle; 4) phosphorylate and activate the pro-apoptotic protein Bad, making it unable to bind to Bcl-2 or Bcl-XL, and thus reducing the occurrence of normal cell apoptosis ( Mayer and Arteaga, 2016 ; Wang et al, 2023e ). In the above study, Sishen Pill improved intestinal inflammatory factors, immune cell disorders, and a series of symptoms of IBD by downregulating the expression of key proteins in the MAPK ( Zhao et al, 2013 ) and PI3K/Akt ( Ge et al, 2020 ; Zhang et al, 2021c ; Liu et al, 2021 ; Liu et al, 2022 ) signaling pathways, and its active metabolites bavachin ( Wang et al, 2023a ), myristicin ( Duan et al, 2020 ), evodiamine ( Chien et al, 2014 ), schisandrin B ( Jiang et al, 2015 ), 8-methoxypsoralen ( Bartnik et al, 2017 ), and schisandrin B ( Dai et al, 2018 ). Consequently, the Sishen Pill could inhibit the progression of colon cancer by regulating the MAPK and PI3K pathways.…”
Section: Discussion On the Common Molecular Mechanism Of Sishen Pill ...mentioning
confidence: 99%
See 2 more Smart Citations